2014
DOI: 10.1007/s10393-014-0974-3
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitoes as a Potential Vector of Ranavirus Transmission in Terrestrial Turtles

Abstract: Ranaviruses are significant pathogens of amphibians, reptiles, and fishes, contributing to mass mortality events worldwide. Despite an increasing focus on ranavirus ecology, our understanding of ranavirus transmission, especially among reptilian hosts, remains limited. For example, experimental evidence for oral transmission of the virus in chelonians is mixed. Consequently, vector-borne transmission has been hypothesized in terrestrial turtle species. To test this hypothesis, mosquitoes captured during a 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Therefore, it is likely that susceptibility of chelonians to ranaviruses differs among developmental stages similar to amphibians . Some outbreaks in box turtles have involved translocation events that congregate many individuals, resulting in high infection prevalence and death (Belzer and Seibert 2011 ;Farnsworth and Seigel 2013 ;Kimble et al 2014 ). In a multiyear survey of box turtles in the USA, ranavirus prevalence has not been reported above 5 % in a population without abnormal mortality events (Allender et al 2013 ).…”
Section: Outbreaks In Cheloniansmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is likely that susceptibility of chelonians to ranaviruses differs among developmental stages similar to amphibians . Some outbreaks in box turtles have involved translocation events that congregate many individuals, resulting in high infection prevalence and death (Belzer and Seibert 2011 ;Farnsworth and Seigel 2013 ;Kimble et al 2014 ). In a multiyear survey of box turtles in the USA, ranavirus prevalence has not been reported above 5 % in a population without abnormal mortality events (Allender et al 2013 ).…”
Section: Outbreaks In Cheloniansmentioning
confidence: 99%
“…In a multiyear survey of box turtles in the USA, ranavirus prevalence has not been reported above 5 % in a population without abnormal mortality events (Allender et al 2013 ). Reports of single cases and outbreaks in reptiles so far have mainly involved box turtles within North America (De Voe et al 2004 ;Allender et al 2006 ;Johnson et al 2008Johnson et al , 2010Ruder et al 2010 ;Allender 2012 ;Kimble et al 2014 ). While eastern box turtles are primarily terrestrial, they have been shown to spend a considerable amount of time in temporary ponds (Donaldson and Echternacht 2005 ), which may expose them to ranavirus through water or sympatric amphibians (Belzer and Seibert 2011 ;Currylow et al 2014 ).…”
Section: Outbreaks In Cheloniansmentioning
confidence: 99%
See 1 more Smart Citation
“…Allender et al ( 2006 ) speculated that ranaviruses may be transmitted between chelonians by vectors because the virus is found in circulating blood cells in turtles. Kimble et al ( 2014 ) recently detected ranavirus in mosquitoes at a site with ranavirus-infected eastern box turtles. Mosquito transmission might help explain how ranaviruses continue to spread between turtles that rarely encounter one another and die fairly quickly from infection.…”
Section: Ranavirus Transmission Within a Speciesmentioning
confidence: 99%
“…Therefore, it is likely that susceptibility of chelonians to ranaviruses differs among developmental stages similar to amphibians . Some outbreaks in box turtles have involved translocation events that congregate many individuals, resulting in high infection prevalence and death (Belzer and Seibert 2011 ;Farnsworth and Seigel 2013 ;Kimble et al 2014 ). In a multiyear survey of box turtles in the USA, ranavirus prevalence has not been reported above 5 % in a population without abnormal mortality events (Allender et al 2013 ).…”
Section: Outbreaks In Cheloniansmentioning
confidence: 99%